Flashes of UV-C light: An innovative method for stimulating plant defences. - Jawad Aarrouf; Laurent Urban (PLoS ONE)
Leaves of lettuce, pepper, tomato and grapevine plants grown in greenhouse conditions were exposed to UV-C light for either 60 s or 1 s, using a specific LEDs-based device, and wavelengths and energy were the same among different light treatments. Doses of UV-C light that both effectively stimulated plant defences and were innocuous were determined beforehand. Tomato plants and lettuce plants were inoculated with Botrytis cinerea, pepper plants with Phytophthora capsici, and grapevine with Plasmopara viticola. In some experiments we investigated the effect of a repetition of treatments over periods of several days. All plants were inoculated 48 h after exposure to the last UV-C treatment. Lesions on surfaces were measured up to 12 days after inoculation, depending on the experiment and the pathogen. The results confirmed that UV-C light stimulates plant resistance; they show that irradiation for one second is more effective than irradiation for 60 s, and that repetition of treatments is more effective than single light treatments. Moreover a systemic effect was observed in unexposed leaves that were close to exposed leaves. The mechanisms of perception and of the signalling and metabolic pathways triggered by flashes of UV-C light vs. 60 s irradiation exposures are briefly discussed, as well as the prospects for field use of UV-C flashes in viticulture and horticulture.